THE EFFECT OF ADVERTISEMENT AND PROMOTION ON BRAND SWITCHING BEHAVIOR OF MOBILE PHONE PROVIDERS IN MANADO - Runturambi, Fallonia; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Companies should pay attention to advertisement and promotion of its brand in order to attract consumers, so, it will influence the brand switching behavior of consumers in choosing mobile phone provider. The aim of this research is to analyze the effect of advertisement and promotion on brand switching behavior. To achieve the objectives, the research method used is associative with multiple regression analysis. The population observed is people who are users of mobile phone providers in Manado with sample as many as 100 respondents. Results and conclusion show that advertisement and promotion have significant impact on brand switching behavior. Advertisement does not have positive and significant impact on brand switching behavior of mobile phone providers. Promotion has positive and significant impact on brand switching behavior of mobile phone providers. The findings of this research is strongly recommended that for mobile phone provider to simultaneously incorporate both Advertisement and Promotion in order to acquire new users or even for users of other brands to have a change of choice. Â  Keywords: advertisement, promotion, brand switching, consumer behavior